Implications of continuous positive airway pressure on heart rate variability in patients with obstructive sleep apnea: Does gender matter? - Bülent Özlek (Türk Kardiyoloji Derneği Arşivi, 2020)
Objective: This study was designed to determine the effectiveness of continuous positive airway pressure (CPAP) treatment on the improvement of heart rate variability (HRV) and whether gender plays a role in HRV in patients with mode-rate to severe obstructive sleep apnea syndrome (OSAS). Methods: Consecutive patients with recently diagnosed moderate to severe OSAS underwent continuous synchronized electrocardiographic monitoring and were prospectively considered for inclusion in the study. HRV was analyzed before starting CPAP therapy and 1 year thereafter. The effects of CPAP on HRV were evaluated in men and women separately to ascertain whether there are gender differences in the clinical manifestations of OSAS and whether female HRV responses to CPAP are similar to those of men. Results: A total of 18 patients (10 men, median age: 56 years) were included in the study. There were no significant differences in the baseline clinical characteristics of the male and female patients. After 1 year of CPAP treatment, heart rate decreased (p<0.05) and time domain parameters increased (p<0.05) in both men and women. None of the frequency domain parameters changed in women (p>0.05), whereas the high frequency power measured increased (p<0.05) and the ratio of low frequency to high frequency decreased (p<0.05) in men after 1 year of CPAP treatment. The increase in HRV after 1 year of CPAP therapy was significantly higher in men than in women (p<0.05). Conclusion: CPAP therapy reduced enhanced cardiac sympathetic nerve activity in patients with OSAS assessed according to HRV. The beneficial effect of long-term CPAP therapy on HRV was more pronounced in men.